Emancipation of the nomenclature as a catalyst for the breakup of the Soviet Union (Economic and Political Thought, 2017)
In December 1991 the Union of Soviet Socialist Republics broke up.Researchers of this problem have classified factors that led to the break-upof the USSR. There are several groups of such causes: ideological, political,social, economic, nomenclature or national ones. The essence of this articlewill be the presentation of the emancipation of the Soviet nomenclature atvarious stages of the history of the USSR till the final stage of this process – thedisintegration of the Soviet empire. The emancipation of the nomenclaturewas one of the manifestations of the multi-faceted modernization of theUSSR and its collision with the communist doctrine as an ideology. Variousattempts to reform the Soviet Union, marking epochs in its history, confirmedthe utopian character of Soviet communism in the ideological dimension.The failed reforms of the communist system contributed to the emergence ofvarious interest groups within the growing Soviet nomenclature. These groupswere fiercely competing for power, and in that situation the maintenance ofthe nomenclature consensus, which bound the Soviet empire, became verydifficult. The last attempt to reform communism and the USSR – perestroika– weakened the central authority enough to lead to the strengthening ofparticularism of the nomenclature. As a result of this complex process,a large of the Soviet nomenclature gained independence from the centre,and by entering into alliances or by concessioning national and democraticmovements in union republics, it gained democratic legitimacy and joined thedisassembly of the Soviet Union.